"United in diversity": Does social diversity increase subjective well-being? - Matthias Opfinger (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2014)
The European Union emphasizes the advantages arising from diversity. However, economic studies prove that diversity can lead to detrimental outcomes, ultimately resulting in lower well-being. This paper assesses the direct link between well-being and diversity within a society, in terms of ethnicity, language, and religion. I find that ethnic diversity is linearly and positively related to happiness and life satisfaction. The other dimensions of social diversity and well-being are related in a U-shape. At low levels of diversity an increase reduces well-being. The relationship becomes positive only if diversity is sufficiently high. I argue that a threat to the dominant position of one group prevents the formation of a common identity. If diversity is sufficiently high, the groups have to establish contact which reduces prejudices and helps to form a common identity.
Keywords: I3; Z1; 330; Social Diversity; Common Identity; Group Threat; Tolerant Societies